Impacts of crop level, soil and irrigation management in grape berries of cv ‘Trincadeira’ (Vitis vinifera L.) - Barroso, J.M. (2017)
Berry size and crop yield are widely recognized as important factors that contribute to wine quality. The final berry size indirectly affects the phenolic concentration of the wine due to skin surface-to-berry volume ratio. The effects of different irrigation levels, soil management and plant crop level on growth of ‘Trincadeira’ berries were studied. In order to test the influence of different irrigation levels (rainfed, pre-veraison and post-veraison), different soil management (tillage and natural cover crops) and different plant crop levels (8 and 16 clusters per vine), leaf water potential, skin anthocyanin, polyphenols, berry skin and seed fresh weight were measured in fruits. The segregation of berries into three different berry classes: small, medium and large, allowed to identify different levels of contribution of soil management and irrigation level into berry, skin and seeds ratios. As expected, higher water availability due to irrigation and soil tillage management during berry development induced an increase in berry flesh weight and this was more evident in larger berries; however, berry skin and seed fresh weight remained unchanged. Also, anthocyanins did not show significant differences.